The Ideal Ionic Liquid Salt Bridge for Direct Determination of Gibbs Energies of Transfer of Single Ions, Part II: Evaluation of the Role of Ion Solvation and Ion Mobilities. Issue 9 (7th February 2018) - Ermantraut, Andreas; Radtke, Valentin; Gebel, Niklas; Himmel, Daniel; Koslowski, Thorsten; Leito, Ivo; Krossing, Ingo
Abstract: An important intermediate goal to evaluate our concept for the assumption‐free determination of single‐ion Gibbs transfer energies Δ tr G°(i, S1 →S2 ) is presented. We executed the crucial steps a) and b) of the methodology, described in Part I of this treatise, exemplarily for Ag + and Cl ‐ with S1 being water and S2 being acetonitrile. The experiments showed that virtually all parts of the liquid junction potentials (LJPs) at both ends of a salt bridge cancel, if the bridge electrolyte is an "ideal" ionic liquid, that is, one with nearly identical diffusion of anion and cation. This ideality holds for [N2225 ] + [NTf2 ] ‐ in the pure IL, but also in water and acetonitrile solution. Electromotive force measurements of solvation cells between S1 and S2 demonstrated Nernstian behavior for Ag + concentration cells and constant like cell potentials for solutions with five tested Ag + counterions. Abstract : It′s ideal : A step towards measuring single‐ion Gibbs transfer energies without extra‐thermodynamic assumptions is described. In elementary open‐circuit potential experiments utilizing an ideal ionic liquid salt bridge, virtually all parts of the liquid junction potential between different solvents could be circumvented for Ag + ‐based systems because of the nearly identical diffusion of [N2225 ] + and [NTf2 ] − within the salt bridge and in the medium.